Sexual behaviour reported by a sample of Italian MSM before and after HIV diagnosis - Laura Camoni; Ivano Dal Conte; Vincenza Regine; Anna Colucci; Monica Chiriotto; Vincenzo Vullo; Marina Sebastiani; Laura Cordier; Rosangela Beretta; Josè Ramon Fiore; Mariagrazia Tateo; Mario Affronti; et al. (Istituto Superiore di Sanità, 2011)
In 2006 we conducted a cross-sectional study involving hospital clinical centres in five Italian cities to compare the sexual behaviour of HIV-positive MSM (men who have sex with men) before and after the diagnosis of HIV infection. Each centre was asked to enrol 30 HIV-positive persons aged > 18 years. The questionnaire was administered to 143 MSM on average 9 years after HIV diagnosis. After diagnosis there was a decrease in the number of sexual partners: the percentage of persons who reported having had more than 2 partners decreased from 95.8% before diagnosis to 76.2% after diagnosis. After diagnosis, there was a significant decrease in the percentage of persons who had never (or not always) used a condom with their stable partner for anal sex from 69.2% before diagnosis to 26.6% after diagnosis and for oral-genital sex from 74.8% before diagnosis to 51.7% after diagnosis. Though at-risk behaviour seems to decrease after diagnosis, seropositive MSM continue to engage in at-risk practices: one fourth of them did not use a condom during sexually transmitted infections (STI) episodes, 12.5% of the participants had had sex for money, and 8.4% had paid for sex. The study shows that our sample of Italian HIV-positive MSM, though aware of being infected, engage in sexual behaviours that could sustain transmission of HIV and other STIs. The results could constitute the first step in implementing national prevention programs for persons living with HIV.